Tenability of ram semen - Oláh, János; Pécsi, Tamás; Kovács, András; Pécsi, Anna; Jávor, András (Acta Agraria Debreceniensis, 2008)
It could be stated that the diluted semen of Awassi rams taken in the breeding season preserved its fertilizing abilityat different temperatures for different periods of time. The motility of spermatozoa kept at 23 vs. 8oC was checked daily. The largest spread of data was observed 24 hours after taking the semen, then the motility rate of cells showed a linear decrease. Motility results of fresh and frozen-thawed samples were compared also after heat resistance test and significant differences were found between these groups. Significant individual differences were observedin the sperm motility after heat resistance test.